2010
DOI: 10.1038/ejcn.2010.53
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of cardiorespiratory fitness, birth weight and parental BMI on adolescents’ obesity status

Abstract: Background/Objectives:The aims of this study were as follows: (1) to analyze differences in cardiorespiratory fitness (CRF), parents' body mass index (BMI) and birth weight (BW) between non-overweight (NOW) and overweight/obese (OV/OB) adolescents, and (2) to investigate the association of those variables with the risk of their biological offspring being OV/OB. Subjects/Methods:This study comprised 788 adolescents (477 girls and 311 boys), aged between 12 and 18 years. CRF was predicted by maximal multistage 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 43 publications
1
9
1
3
Order By: Relevance
“…Time spent in LPA, VPA, and VHPA increased significantly more during free days than school days between PS and JHS, while MPA significantly decreased. The present data differed from those reported by Gavarry et al (2003), but were in agreement with those reported by Trost et al (2002), Wilkin et al (2006), and Vale et al (2010). Gavarry et al (2003) observed that at primary' school the time engaged in MPA to VPA was longer during school days than during free days for young boys; however, adolescents did not show higher levels of MPA and VPA on school days than on free days.…”
Section: Day Of the Weekcontrasting
confidence: 54%
See 2 more Smart Citations
“…Time spent in LPA, VPA, and VHPA increased significantly more during free days than school days between PS and JHS, while MPA significantly decreased. The present data differed from those reported by Gavarry et al (2003), but were in agreement with those reported by Trost et al (2002), Wilkin et al (2006), and Vale et al (2010). Gavarry et al (2003) observed that at primary' school the time engaged in MPA to VPA was longer during school days than during free days for young boys; however, adolescents did not show higher levels of MPA and VPA on school days than on free days.…”
Section: Day Of the Weekcontrasting
confidence: 54%
“…The latter concluded that differences were due to the intensity of the most frequent bouts and the frequency of the most intense bouts of activity. Vale et al (2010), with a 5-s monitoring epoch reported that preschoolers were more active during school days than free days. Portuguese children showed higher scores in time spent from MPA to VHPA than young French ones (128 min and 120 min, for school days and free days, respectively).…”
Section: Day Of the Weekmentioning
confidence: 96%
See 1 more Smart Citation
“…It remains uncertain whether this lack of association between birth weight and adiposity may be explained in part by the use of crude measures of adiposity such as BMI. Conversely, a previous study found that girls with high birth weight, low fitness level, and at least one parent with overweight were significantly more likely to be classified as overweight/obese at age 12–18 years [29]. However, important confounders such as sexual maturation, gestational age, and dietary factors were not taken into account.…”
Section: Discussionmentioning
confidence: 99%
“…O nível socioeconômico e educativo dos pais, maus hábitos alimentares, inatividade física e poucas horas de sono estão relacionados com uma maior probalidade de crianças e adolescentes serem obesos (4) . Uma evidência atual demonstra que filhos de pais obesos apresentam risco mais elevado de obesidade devido a genes e ambientes compartilhados, ou seja, aumenta o risco de uma criança se tornar um adulto obeso independente do estado de gordura na infância (8) , já que a obesidade infantil está diretamente associada à obesidade na vida adulta (9) . Uma boa alimentação aliada à prática de atividades físicas faz toda a diferença no peso da criança, do adolescente e também do adulto.…”
Section: Introductionunclassified